Implementation of the Principles of Legal Certainty and the Principles of Justice towards Tax Amnesty II Policy on Voluntary Tax Disclosure - Ahmad Zumar Syafiq; Suparnyo (Dinasti Research, 2024)
This research is motivated by the existence of a voluntary tax disclosure policy that creates a gap that is considered unfair between individual taxpayers who are compliant and less compliant. Of course, this has an impact on discrimination and bias between one party for taxpayers. The purpose of this study is to determine the implementation of the principle of legal certainty and the principle of justice for individual taxpayers who participate in the voluntary disclosure programme at the Kudus Regency Tax Office. The research approach is non-doctrinal (socio-legal approach). The data used comes from interviews and documentation. The data is presented in the form of analytical descriptions. The results of the study indicate that the Tax Amnesty policy related to the Voluntary Tax Disclosure Program that has been held at the Kudus Regency Tax Office if analyzed using Hans Kelsen's theory in terms of legal certainty is appropriate, while the analysis of the aspect of justice in the theory of John Rawls and Gustaf Radbrch there is injustice for taxpayers and can cause discrimination. This article contributes to a deeper understanding of the voluntary disclosure programme by exploring the views of taxpayers from the perspective of taxpayers and analysing the implementation of the voluntary disclosure programme.